CROP IMPROVEMENT THROUGH INDUCING MUTAGENESIS IN VIVO USING COLCHICINE ON COWPEA (Vigna unguiculata L. Walp) - Susrama, I Gede Ketut; Wirawan, I Gede Putu (International Journal of Biosciences and Biotechnology; Vol 4 No 2 (2017), 2017)
Colchicine treatments of 0.005% and 0.01% either in distilled water or in hydrogen peroxide 3% were caused temporary leaf shape changes on cowpea. Treatment of colchicine in hydrogen peroxide 3% resulted in green pod color change to purple however treatment of just hydrogen peroxide 3% and colchicine in hydrogen peroxide 3% caused 8.8-10.7% dwarf cowpea. As a preliminary data, we also observed that cowpea crops grown from seeds treated with colchicine in distillate water attacked by bean leaf beetle much earlier compare to the treatment with colchicine in hydrogen peroxide 3%.